Love in the time of Bertie [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- 44 Scotland Street series, 2022)
"In the microcosm of 44 Scotland Street, all of life's richness is found in the glorious goings-on of its residents. There's Domenica, whose anthropological training has honed her observations of her neighbors; Matthew, whose growing triplets are more than a handful; Bruce, whose challenge as ever is thinking of anything but himself; and Big Lou, who may just have found her shot at romance. And of course, there's young Bertie Pollock, whose starry-eyed explorations of Edinburgh's New Town are a touching reminder that life itself is an adventure and there's joy to be found wherever you choose to look."--